To embrace or not to embrace? Understanding public's dilemma about autonomous mobility services: A case study of Singapore. Issue 4 (December 2021) - Chng, Samuel; Anowar, Sabreena; Cheah, Lynette
Highlights: Understanding public dilemma about autonomous mobility services. Insights from a survey and citizen debate in Singapore. Strengthen trust by addressing concerns and uncertainty surrounding AV technology. The public seeks clearer clarification on liability and assurance of rigorous testing. Abstract: One of the key challenges to Autonomous Vehicle (AV) adoption and realization of the benefits is how the general public perceives the technology and how willing or unwilling they are to accept it. However, research focusing on understanding user's perception and acceptance is still incipient, despite the recent proliferation of literature on autonomous mobility. In our study, we aim to address the gap in the literature using Singapore as our case study. Instead of relying on a single source of data, we draw and compare results from two different data sources collected using different methodologies – a survey and a public engagement event – to explore preferences about the impending introduction of AVs in public transport. Top three implementation preferences found both in the survey and debate samples include: 1) clearer clarification of liability in case an accident occurs, 2) implementing a public education campaign on how the autonomous technology works and what the possibilities and limitations are, and 3) having AVs tested on the roads by the authorities first before making available to the public. We also found that trust in AVs exist in this context; this trust can be further strengthened through addressing the concerns and uncertainty surrounding AV technology as identified in the paper.